Types of feedback used by teachers to develop the english speaking skill on the students of Advanced Intensive English level at the Foreign Language Department of the University of El Salvador, main campus. - Castaneda López, Sara Ibeth; Barahona Muñoz, José Victorino; Landaverde, Alexander (San Salvador, El Salvador : Universidad de El Salvador, 2016)
In recent years, the number of people learning English has increased due to several reasons. One of the most influential ones seems to be that during the last five years many outsourcing companies which carry out their transactions mostly in English have established their usinesses in El Salvador. Another reason why people learn English might be due to the fact that national small businesses in El Salvador continue to grow and their services and products are being distributed abroad, so such companies require their personnel to be competent in the English language. Since English is not the mother tongue in El Salvador, people need to find specialized institutions to learn it. One of those institutions is the Foreign Language Department at the University of El Salvador. This department has three different majors that are offered in English including one with a specialized major in teaching. There is another major in Modern Languages specialized in English and French, and a Teachers` training program that educates people for being teachers to work at secondary school levels. The two majors and the Teachers´ Training program before mentioned provide a set of courses that accomplish the students´ necessities by giving them a professional guide. This guide begins from basic levels, goes through the intermediate ones, and finishes in the advanced levels. It is on the advanced courses that this research is focused on. Since the advanced English courses require the students to manage a competent English level, they need to be able to communicate with fluency, use the appropriate structures and have a variety of vocabulary; there arises a question about how teachers work in order to develop and improve their students´ performance, especially in speaking. This research project is focused on what types of feedback are used by teachers to develop and maintain the speaking skill (one of the four English macro skills) in the Advanced English cours
Incluye apendices.
Tesis para optar al titulo de -- (Licenciatura en Idioma Inglés Opción Enseñanza) -- Universidad de El Salvador, San Salvador, 2016
Bibliografía 76-78
Audiencia general.
Keywords: What is feedback; Types of feedback; Feedback Strategies